DEVELOPMENT OF BULLETIN AS A LEARNING MEDIA ON ELECTROLYTE AND NON-ELECTROLYTE SOLUTION MATERIALS IN CLASS X MAS DARUL IHSAN ACEH BESAR - Wildan Mabrura; Zulfadli Zulfadli; Latifah Hanum (FKIP USK, 2020)
This study aims to develop, analyze the feasibility and describe the responses of students and teachers according to the newsletter learning media on electrolyte and non-electrolyte solution material. This type of this research is (Research and Development/ RD). The newsletter learning media developed in this study according to ADDIE model which has five stages: (1) analysis, (2) design,(3) Development (4) Implementation and (5) Evaluation. This research was conducted at the school of MAS Darul Ihsan Aceh Besar with 3 chemistry teachers and 31 students taken from class X. The appropriateness of the newsletter media was assessed by the research supervisor. The percentage of teacher and student responses to the newsletter media that was developed was 97.22% and 83.97% with the very good category. Based on the results of the study, it can be concluded that the developed newsletter media is very suitable for use in the learning process of electrolyte and non-electrolyte solution materials.